POLLINATORS INSECTS IN Theobroma cacao L. PRODUCTION SYSTEMS IN THE CENTRAL AREA OF THE ECUADORIAN LITTORAL - Armijos Vásquez, Vivianna (2020)
Natural pollinators follow an important role in the reproductive efficiency of Theobroma cacao L. The objective of this research was to determine the quantity and diversity of insects in T. cacao National Type, in monoculture system and agroforestry system, with emphasis on pollinators. The study was carried out in the experimental farm “La Represa” located in the city Quevedo, province Los Ríos, Ecuador. Emergency traps and insect capture were placed in the two farming systems. In addition, direct observations were made on the flowers of T. cacao to record the presence of pollinating insects. The captured insects were identified with the help of entomological keys, magnifying glass, and stereomicroscope. The Simpson dominance and diversity index and Jaccard similarity index were calculated. The highest percentages of insects were obtained from the order Hymenoptera (76.99%), Coleoptera (10.21%) and Diptera (7.95%). The Simpson index was calculated at 0.58 and 0.42, and Jaccard’s similarity was 24% among insect families found in both production systems. A single family (Cecidomyiidae) was recorded as a possible pollinator in T. cacao in the study area. There is low diversity and high dominance of insects for the production systems analyzed. One of the climatic factors that influences the presence of the insects captured in T. cacao is the relative humidity, since a positive direct relationship was found between these two variables